Analysis of radial breathing-mode of nanostructures with various morphologies: a critical review. (3rd August 2015) - Ghavanloo, E.; A. Fazelzadeh, S.; Rafii-Tabar, H.
<x content-type="archive" xml:space="preserve">Abstract</x> Knowledge about the vibrational characteristics of nanostructures is of fundamental interest, since it is a signature of their morphology and it can be utilised to predict their material properties. Radial breathing-mode (RBM) is a special vibrational mode, displayed by the nanostructures, and can be observed experimentally. Over the past two decades, the study of the RBM of the nanostructures has attracted much attention because of its importance in such applications as structural and material property characterisations. This paper reviews recent theoretical and experimental studies on the RBM frequencies of nanostructures with various morphologies. There is a one-to-one correspondence between the geometrical characteristics of the nanostructures and their RBM frequencies. An overview of the current literature discussing the RBM frequency of carbon nanostructures and their geometrical characterisation is presented first. Authors then discuss the theoretical and experimental studies on the breathing-modes of spherical nanoparticles. Different approaches, which have been utilised to obtain the RBM frequency of circular nanowires, are then reviewed. Finally, conclusions and recommendations for further research in this field are provided. To the best of our knowledge, a specialised review addressing the RBM of the nanostructures has not been available so far. This work is likely to fill this gap.